penggunaan bahasa ibu dalam keterampilan berbicara pada pembelajaran bahasa indonesia - pratimi ismiani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is a communication tool that is conveyed orally or in writing. Language can be seen from speaking skills, for example the language used is good or bad. Indonesian is intended so that students can use good and correct language, can use polite and non-offensive language. The research conducted aims to determine the use of mother tongue in speaking skills in Indonesian language learning in the classroom. The method used is a qualitative descriptive research method with data collection in the form of observation, and recording tools, the observation function is to determine the speaking skills of students using their mother tongue in Indonesian language learning, while the recording tool is to determine the use of mother tongue in learning. In Indonesian language learning, students use their mother tongue more (Sundanese), because students think their mother tongue is more understood and understood. The results of research in class X 99% of students use their mother tongue. The factors that influence the mother tongue in learning are school environmental factors, environmental factors where students live, and the lack of vocabulary that students have so that students tend to use their mother tongue compared to Indonesian. The efforts made by this research are so that students can acquire vocabulary and be able to use Indonesian when learning by applying literacy to students by reading non-fiction and fiction books.